2014
DOI: 10.1186/s13059-014-0482-3
|View full text |Cite
|
Sign up to set email alerts
|

Sequence specificity incompletely defines the genome-wide occupancy of Myc

Abstract: BackgroundThe Myc-Max heterodimer is a transcription factor that regulates expression of a large number of genes. Genome occupancy of Myc-Max is thought to be driven by Enhancer box (E-box) DNA elements, CACGTG or variants, to which the heterodimer binds in vitro.ResultsBy analyzing ChIP-Seq datasets, we demonstrate that the positions occupied by Myc-Max across the human genome correlate with the RNA polymerase II, Pol II, transcription machinery significantly better than with E-boxes. Metagene analyses show t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
58
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(66 citation statements)
references
References 65 publications
(83 reference statements)
8
58
0
Order By: Relevance
“…Altogether, in line with previous observations in either B-cells (Guccione, Martinato et al, 2006, Lin et al, 2012, Nie et al, 2012, Sabò et al, 2014 or others (Guo, Li et al, 2014, Kress et al, 2016, Lin et al, 2012, Soufi, Donahue et al, 2012, Walz et al, 2014, Zeid et al, 2018, acute accumulation of Myc upon LPS treatment led to its widespread association with pre-existing promoters and enhancers: this phenomenon, also termed "invasion" (Lin et al, 2012, Nie et al, 2012, Sabò et al, 2014, most probably occurs through low affinity, non sequence-specific interactions with genomic DNA. Together with the findings that Myc deletion only impacts a subset of the genes regulated by either LPS (this work) or serum , we infer that chromatin association cannot be systematically equated with productive regulatory engagement of the transcription factor onto genomic DNA (de Pretis et al, 2017, Muhar et al, 2018.…”
Section: Resultssupporting
confidence: 86%
“…Altogether, in line with previous observations in either B-cells (Guccione, Martinato et al, 2006, Lin et al, 2012, Nie et al, 2012, Sabò et al, 2014 or others (Guo, Li et al, 2014, Kress et al, 2016, Lin et al, 2012, Soufi, Donahue et al, 2012, Walz et al, 2014, Zeid et al, 2018, acute accumulation of Myc upon LPS treatment led to its widespread association with pre-existing promoters and enhancers: this phenomenon, also termed "invasion" (Lin et al, 2012, Nie et al, 2012, Sabò et al, 2014, most probably occurs through low affinity, non sequence-specific interactions with genomic DNA. Together with the findings that Myc deletion only impacts a subset of the genes regulated by either LPS (this work) or serum , we infer that chromatin association cannot be systematically equated with productive regulatory engagement of the transcription factor onto genomic DNA (de Pretis et al, 2017, Muhar et al, 2018.…”
Section: Resultssupporting
confidence: 86%
“…As TAF1 (TATA-Box Binding Protein Associated Factor 1) is associated with transcriptional initiation at the TATA box, one explanation might be that binding sites of these TFs are enriched at core promoters. Indeed, binding to proximal promoters has been reported for MYC/MAX (Guo et al ., 2014), CREB1 (Zhang et al ., 2005), YY1 (Li et al ., 2008), and E2F factors (Rabinovich et al ., 2008).…”
Section: Resultsmentioning
confidence: 95%
“…11,12,15 In fact, it was also demonstrated that the location of c-Myc on chromatin correlates more closely with the location of Pol II rather than that of E-Box sequences. 16 As discussed elsewhere, 15 this is explained by the fact that dimeric b-HLH-LZs bind to nonspecific DNA with significant affinities only one to two order of magnitude lower than for E-box sequences. 16,17 This invasion was further shown to a steady recruitment of the pauserelease factor P-TEFb by c-Myc at the newly bound promoters and enhancers and to the linear amplification of the expression of active transcriptional programs.…”
Section: Introductionmentioning
confidence: 95%
“…16 As discussed elsewhere, 15 this is explained by the fact that dimeric b-HLH-LZs bind to nonspecific DNA with significant affinities only one to two order of magnitude lower than for E-box sequences. 16,17 This invasion was further shown to a steady recruitment of the pauserelease factor P-TEFb by c-Myc at the newly bound promoters and enhancers and to the linear amplification of the expression of active transcriptional programs. 10,15 This nonspecific binding and transcriptional amplification are believed to play a key role in the carcinogenesis processes and to cause to the so-called addiction to c-Myc.…”
Section: Introductionmentioning
confidence: 95%